SOCIAL INFLUENCE TO CONSUMER BUYING DECISION A QUALITATIVE METHOD ON SAMSUNG GALAXY SERIES CUSTOMERS IN MANADO - Rompas, Elwin P; Tumewu, Ferdinand J (Universitas Sam Ratulangi, 2014)
Consumers tend to do a long process of buying decision in order to buy a luxury product, and this process can be influenced by product attribute offered by the product itself or influenced by social references. The purpose of this study is to analyze the factors which influence consumer buying decision of Samsung Galaxy Series customers in Manado. This research was conducted qualitatively through in-depth interview with 30 informants. All the data and information gathered was analyzed using data Tri-angulation which data were gathered from the interview with difference informants, different places of observation, and review from several literatures of various researchers. The result of this study revealed the buying decision of Samsung Galaxy Series in Manado is mostly influenced by product attribute concern such as quality, design and style, feature, advertisement, and service center. Product attribute becomes the judgment tool in order to guide and help the prospective consumer through decision making process. The study also shows the impact of social influences to consumer buying decision through family members nor friend’s persuasion. It is better for management to improve their product development by developing the quality of product and adding creative features based on consumer’s needs and wants. Keywords: consumer buying decision, product attribute, social influence